2017
DOI: 10.1083/jcb.201709115
|View full text |Cite
|
Sign up to set email alerts
|

A toolbox of anti–mouse and anti–rabbit IgG secondary nanobodies

Abstract: Pleiner, Bates, and Görlich introduce anti–mouse and anti–rabbit IgG nanobodies that can be produced in E. coli and fused to reporters or labeled fluorescently to create bright and specific detection reagents with unique advantages over conventional polyclonal secondary antibodies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 38 publications
7
150
0
1
Order By: Relevance
“…Previously, nanobodies were reported to bind primary antibodies from mouse and rabbit as host species for super‐resolution microscopy . Inspired by this, we introduce here the use of DNA‐conjugated bacterially derived protein A (molecular weight 46 kDa) and protein G (molecular weight 22 kDa) molecules as small binders for primary antibodies in combination with DNA‐PAINT super‐resolution microscopy (Figure ).…”
Section: Figurementioning
confidence: 99%
“…Previously, nanobodies were reported to bind primary antibodies from mouse and rabbit as host species for super‐resolution microscopy . Inspired by this, we introduce here the use of DNA‐conjugated bacterially derived protein A (molecular weight 46 kDa) and protein G (molecular weight 22 kDa) molecules as small binders for primary antibodies in combination with DNA‐PAINT super‐resolution microscopy (Figure ).…”
Section: Figurementioning
confidence: 99%
“…Since the preliminary results indicated that their anti-Bacilus anthracis nanobodies were stable and functional intrabodies, Anderson et al [103] expressed them fused to beta galactosidase directly in the cytoplasm of Tuner (DE3) E. coli. Shibuya et al [105] managed to coexpress in bacterial cytoplasm nanobodies fused to complementary split intein moieties for obtaining bispecific VHH constructs by in-cell transsplicing whereas nanobodies engineered with extra cysteines or ascorbate peroxidase were functionally recovered after production in NEB express F' cells [39]. Another nanobody with intrabody features has been generated to bind to the ALFA-tag and was effectively used to detect in vivo interactions and pull-down experiments [106].…”
Section: Bacterial Cytoplasmmentioning
confidence: 99%
“…Unluckily, a direct comparison between the results obtained with conventional wetlab approaches (based on random mutagenesis of the initial candidates followed by more stringent in vitro selection steps) and in silico modeling has not yet reported but it would be interesting to evaluate the necessary efforts, resources and achievements specific of the two alternatives. Considering what has been already accomplished with conventional antibodies [122], the available data suggest that a smart conventional approach can still assure results that no in silico system has provided so far [39] but algorithms become progressively more competitive. The following examples show some encouraging results of in silico protocols that follow different strategies to anticipate the potential effect of specific (multiple) single mutations.…”
Section: In Silico Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that these boron probes are potential labeling probes for total and specific molecular imaging using non-optical nanoSIMS.T he probes work as small tags,w hich can be directly coupled to their targets, either by co-translational incorporation of alkyne-modified amino acids followed by click chemistry or by immunostaining with nanobodies.T his should also enable their use in amore general way,byc oupling similar probes to secondary nanobodies [30] (directed against mouse or rabbit antibodies), which should render the probes immediately applicable in any type of antibody-based imaging and in any type of sample.…”
Section: Angewandte Chemiementioning
confidence: 99%